2007
DOI: 10.1002/pits.20260
|View full text |Cite
|
Sign up to set email alerts
|

Social skills interventions for children with autism

Abstract: Autism is characterized by deficits in pretend play, perspective taking, initiating and responding to others, and other profound social impairments. As the incidence of children being identified with autism increases, so does the need for effective interventions that target social skills development. Over the last decade, social skills interventions have become more sophisticated, incorporating video technology and naturalistic teaching procedures. Many of these studies have been shown to generalize across set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 35 publications
1
54
0
Order By: Relevance
“…"nimal-assisted interventions ""I) have started to be approached by specialists designing therapeutic programs for children with social impairments, such as "SD children, which appear to perceive and comprehend animal communication beter than the human communication [9,10]. It is generally acknowledged that one of the most important deicits that "SD individuals experience across their life span is the impairment in social abilities [11]. Recently, several authors in the "SD ield suggested that the use of all the possible elements of social environment, including companion animals, should be considered when planning therapeutic interventions for "SD children [10].…”
Section: Social Story In the Presence Of Dogs: An Animal-assisted Ementioning
confidence: 99%
See 4 more Smart Citations
“…"nimal-assisted interventions ""I) have started to be approached by specialists designing therapeutic programs for children with social impairments, such as "SD children, which appear to perceive and comprehend animal communication beter than the human communication [9,10]. It is generally acknowledged that one of the most important deicits that "SD individuals experience across their life span is the impairment in social abilities [11]. Recently, several authors in the "SD ield suggested that the use of all the possible elements of social environment, including companion animals, should be considered when planning therapeutic interventions for "SD children [10].…”
Section: Social Story In the Presence Of Dogs: An Animal-assisted Ementioning
confidence: 99%
“…In the case of "SD children, specialists agree that social impairment does not necessarily imply a lack of desire or interest of children to socially interact, but rather a lack of necessary social skills to successfully carry out social interactions [11]. In this direction, several types of interventions are focusing on improving the social skills of "SD children, and among them, Social Story [8] is one of the most popular methods used in special education in general and in the treatment of autism, in particular.…”
Section: Social Story In the Presence Of Dogs: An Animal-assisted Ementioning
confidence: 99%
See 3 more Smart Citations